Intercultural, Ecumenical and Interreligious Dialogue: An Introduction - Anthony, Francis-Vincent (Religions, 2023)
Religious traditions with their universal intent on human salvation or well-being have de-territorialized themselves or migrated from the place of their origin along trade routes in the company of merchants, invaders, and colonizers [...]